Prerequisites defining the trajectory of creative thinking - M. K. Suyundikova; E. O. Zhumataeva; M. M. Suyundikov; E. I. Snopkova (Russian State Vocational Pedagogical University, 2021)
Introduction. The modern, rapidly changing world needs specialists with creative thinking skills, who are able to show rapidity, flexibility and originality in solving complex and extraordinary problems. When a specialist finds himself in such a situation where he faces extraordinary problems, he does not know how to solve them and is at a loss. It is impossible to acquire creative thinking skills without preparation. Therefore, a student, a future specialist, must be taught these skills. However, the difficulty lies in the fact that without developing students' skills such as analysis, synthesis, abstract, associative and combinatorial thinking, selective comparison, generalisation of information, system vision, assessment of ideas, the ability to ask right questions, to visualise and to draw conclusions, it will be difficult to further develop creative thinking in students.Aim. The aim of the study is to discover the relationship between various types of thinking and creative thinking, to determine the types of thought operations and the list of prerequisites that precede creative thinking, which will contribute to the formation of creative thinking in students.Methodology and research methods. General logical reasoning methods and some scientific research methods were applied. The phenomenological method was employed to understand the process of creative thinking. Based on the determination of the main parameters and properties of each type of thinking, it became possible to model the process of creative thinking activity, to investigate this mental process and draw certain conclusions. The use of the explanatory method also makes it possible to substantiate the need for the following prerequisites for the formation of creative thinking.Results and scientific novelty. Based on the analysis, it was discovered that various types of thinking are related to creative thinking, the types of thought operations were determined and a list of prerequisites was proposed. The list of prerequisites includes the following types of thinking: positive, synergetic, associative, abstract, visual, algorithmic, divergent, lateral, Janusian, questioning style, combinatorial, intuitive, systemic, and critical. The research results show the importance and necessity of prerequisites for creative thinking and also determine the trajectory of creative thinking activity.Practical significance. The research results can be useful for teachers of higher educational institutions with the aim of applying them in the learning process.